Retrofitting and renovation of worn-out textures, re-creation or rupture of identity - Mohammadibrahim Mazhari (مهندسی و مدیریت ساخت, 2021)
This research paper is about the solutions of giving identity to architectural spaces, strengthening the sense of belonging of the residents to their place of living and as a result, expanding their sense of participation in the implementation of plans for organizing and renovating worn-out urban tissues. Organizing and renovating worn-out urban tissues is a combination of social, cultural and physical processes that should be seen in a comprehensive plan. In addition, the renovation program should be based on long-term goals so that it can eliminate the areas of non-acceptance in the society by considering possible changes in the future. In order to achieve the goals of empowering and improving the quality of life in worn-out urban contexts, paying attention to maintaining and revitalizing the neighborhood system, helping to increase the sense of belonging of the residents to their place of residence, and also strengthening the local community in order to expand the sense of people's participation in the implementation of projects is of particular importance. In relation to the topic of the research, the basic question is: Does the sense of belonging of the residents to their place of residence have an effect on their participation in the implementation of projects? Clarifying the problem and answering the theoretical dimensions of identity and sense of belonging and searching for scientific gaps in facing the improvement and reconstruction of worn-out urban tissues is of great importance, because the city is a living entity and has a living body and soul. Renovation with the concept of contemporization and re-creation is the reproduction of the urban environment in new conditions. Reproduction includes revising and restoring values in their contemporization.